Real-Time Imaging of Fluorescent Flagellar Filaments - Turner, Linda (American Society for Microbiology, 2000)
Bacteria swim by rotating flagellar filaments that are several micrometers long, but only about 20 nm in diameter. The filaments can exist in different polymorphic forms, having distinct values of curvature and twist. Rotation rates are on the order of 100 Hz. In the past, the motion of individual filaments has been visualized by dark-field or differential-interference-contrast microscopy, methods hampered by intense scattering from the cell body or shallow depth of field, respectively. We have found a simple procedure for fluorescently labeling cells and filaments that allows recording their motion in real time with an inexpensive video camera and an ordinary fluorescence microscope with mercury-arc or strobed laser illumination. We report our initial findings with cells of Escherichia coli. Tumbles (events that enable swimming cells to alter course) are remarkably varied. Not every filament on a cell needs to change its direction of rotation: different filaments can change directions at different times, and a tumble can result from the change in direction of only one. Polymorphic transformations tend to occur in the sequence normal, semicoiled, curly 1, with changes in the direction of movement of the cell body correlated with transformations to the semicoiled form.